Influência da imunoexpressão de proteínas do complexo Mismatch Repair na sobrevida livre de doença em carcinomas de células escamosas de orofaringe tratados não cirurgicamente - Coelho, Lívia Moreira Caetano (2024)
Introduction: Cancer represents a great concern due to its high incidence and elevated mortality rates, with oropharyngeal squamous cell carcinoma (OSCC) showing increasing rates, mainly associated with human papillomavirus. Current studies on the DNA mismatch repair (MMR) pathway have emerged to associate the dysfunction of this pathway with the development or progression of cancers. Objective: To evaluate the influence of immunoexpression of MMR complex proteins on disease-free survival in non-cirurgically treated oropharyngeal SCC. Materials and methods: Eighty-five cases of oropharyngeal SCC diagnosed and treated at Hospital Haroldo Juaçaba/Ceará Cancer Institute were analyzed. Clinicopathological data and paraffin blocks from incisional biopsies were retrieved for immunohistochemical reactions for MSH2, MSH6, PMS2, MLH1 and p16. Ten microscopic fields of each sample were evaluated for the percentage of labeled cells. Disease-free survival was calculated, and statistical analyses included Kruskal-Wallis and Friedman/Dunn tests, chi-square and Fisher's exact tests, Log-Rank Mantel-Cox and Cox regression (SPSS 17.0, p<0.05). Results: The majority of sample were women (n=62, 72.9%), aged over 60 years (n=33; 66.0%), in stage T4 (n=47; 55.3%) and had lymph node involvement (n=52; 61.25%). All patients underwent radiotherapy. Seventeen (20.0%) were p16+ and 68 (80.0%) were p16-. Most patients reported smoking (n= 73; 85.9%) and/or alcohol use (n= 61; 71.8%). Perineural invasion was present in 2 cases (2.4%) and angiolymphatic invasion in 25 cases (29.4%). In p16- tumors, the loss of MSH2 expression was associated with shorter disease-free survival (p=0.035) and the mean expression of MSH6 was significantly higher than that of MSH2 (p=0.001). Loss of MSH2 expression in p16+ tumors was associated with longer disease-free survival compared to p16- tumors. An MSH6/MSH2 imbalance in p16+ tumors was associated with longer survival compared to p16- tumors. The MLH1/PMS2 imbalance was significantly higher in p16+ tumors with recurrence (p=0.003). In multivariate analysis, low MSH2 immunoexpression increased the risk of recurrence by 9.10 times (95%CI 1.99 to 83.06). Conclusion: Microsatellite instability in oropharyngeal SCC is demonstrated, particularly by the association between the loss of protein expression and their heterodimer imbalance with disease-free survival.